Influence of oviduct cell secretions cultured in vitro on the viability of frozen-thawed bovine sperm cells - Valleriote, Patrícia; Paes de Carvalho, Carla; Dubeibe , Diego Fernando; Mogolllón , Edgar Mauricio; Burla , Angelo Jose (Spei Domus, 2015)
Introduction: in cattle, the oviduct is essential in the process of maturation, fertilization and acquisition of competence for proper development of an embryo until the blastocyst stage. Once the cells in the internal lining of the oviduct provide substances that positively affect sperm as it crosses the female genital tract, the surface components are modified or removed by secretions present therein. Such modifications may include cholesterol depletion on sperm surface, altered glycosaminoglycans, and change in ions. Methodology: the objective was to evaluate the influence of adding cell culture medium of bovine oviduct cells on sperm parameters such as motility, vigor, and integrity of cytoplasmic membrane. The sperm cells were incubated with 164 μl of Talp-sp-Uso in the control group (TCt); 161.5μl of Talp-sp-Uso, in addition to 2.5μl of heparin (20μg/ml) in treatment 1 (THep) and 128μl of Talp-sp-Uso, along with 36μl of culture medium with secretions of bovine oviduct cells in treatment 2(TOv). Tests were performed at zero time (to show that the medium of treatments did not hurt the sperm cells) and after three hours of incubation. Results: no significant differences in progressive motility, vigor and integrity of cell membrane between treatments were found. However, sperm cells cultured with oviduct cell secretions showed a greater percentage of total motility after three hours of culturing, in contrast to sperm cultured in the presence of heparin. Conclusion: oviduct cell secretions do not affect progressive motility, vigor or integrity of the cytoplasmic membrane of sperm cells; however, they prolong sperm motility.